A graphene oxide coated sulfide-based solid electrolyte for dendrite-free lithium metal batteries. (15th June 2021) - Li, Jianwei; Li, Yuanyuan; Cheng, Jun; Sun, Qing; Dai, Linna; Nie, Xiangkun; Chen, Lina; Han, Guifang; Ci, Lijie
Abstract: Sulfide-based solid electrolyte is one of the most promising solid electrolytes due to its high ionic conductivity and wide electrochemical window. However, it suffers from serious interfacial issues with lithium metal, which hinder the lithium-ion transport during cycling process and increase the interfacial resistance and instability. Protection only from Li anode side is not enough since Li enters into the bulk solid electrolyte resulting reaction and dendrite growth. Herein, we design a graphene oxide (GO) coated solid electrolyte Li7 P3 S11 particles for stable and efficient all-solid-state battery application. The GO could partially isolate the Li7 P3 S11 solid electrolyte from lithium metal. Meanwhile, the GO or rGO reduced by Li guide the homogeneous growth of Li and increase the cycling stability. Our work provides a facile method to fully protect Li7 P3 S11 in three directions from reaction with Li metal for dendrite-free and highly stable sulfide-based all-solid-state battery applications. This work might inspire the community with new material engineering/design strategies toward practical application in highly stable all solid state lithium-ion batteries. Graphical abstract: GO and LPS composite solid electrolytes were successfully synthesized using a solution synthesis method. The assembled Li/1% GO@Li7 P3 S11 /Li symmetrical cell can stably plating/stripping for over 300 cycles at 0.1 mA cm −2 at 25 °C. Image 1